Dari Dapur Ke Komunitas: Peran Kader Perempuan Dalam Membangun Ketahanan Gizi Anak Di Desa Lahan Kering Nusa Tenggara Timur - Bire Manoe, Lenny Sofia; Roen, Yeheskial Adrian; Sabariman, Hoiril; Perangin Angin, Imanta I. (IJouGS: Indonesian Journal of Gender Studies, 2025)
Malnutrition, particularly stunting, remains a major challenge in dryland regions such as East Nusa Tenggara (NTT). This area faces a range of constraints, including structural issues, limited access to nutritious food, a clean water crisis, restricted access to health services, and a lack of education and proper parenting practices—especially among women. This article analyzes the crucial role of women cadres, particularly those involved in Posyandu (Integrated Health Posts), Women Farmers Groups (KWT), and the Family Welfare Empowerment movement (PKK), as key agents of change in improving children's nutritional resilience, which in turn contributes to reducing stunting rates. This study employs a descriptive qualitative approach, using literature review as the primary data collection method. Data were gathered from journal articles, books, and research reports, which were then synthesized and presented narratively. The findings reveal that, despite the ecological limitations of dryland areas like NTT—characterized by short planting seasons, low rainfall, and limited water and food resources—village women cadres play a strategically significant dual role in improving child nutrition. Based on their dual function as managers of both the household "kitchen" and the village "community," these women transform local knowledge, dryland food resources, and nutrition education into sustainable daily practices. Their roles encompass nutrition and health education, local food-based dietary diversification, and advocacy at the village level. Empowering women cadres has proven to be an effective adaptive strategy to address nutritional vulnerabilities driven by the ecological challenges of dryland areas.